2007
DOI: 10.1080/03014460701452868
|View full text |Cite
|
Sign up to set email alerts
|

The height of women in Sub-Saharan Africa: The role of health, nutrition, and income in childhood

Abstract: Changes in cohort adult height over time in Sub-Saharan Africa are related to changes childhood health and nutrition, although variation across countries appears to be determined mainly by unexplained fixed factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 27 publications
5
45
0
1
Order By: Relevance
“…For example, African women are the tallest in the developing world but they grow up in very poor conditions (Deaton, 2007). Nevertheless, cohort variation in height within sub-Saharan Africa is sensitive to indicators of the early life nutritional environment (Akachi and Canning, 2007). We have confirmed that this is also the case in the current sample, where birth year GDP, the regional infant mortality rate and the average education of mothers in the cohort influences the height of adult women (Bhalotra 2009).…”
Section: Maternal Healthsupporting
confidence: 72%
“…For example, African women are the tallest in the developing world but they grow up in very poor conditions (Deaton, 2007). Nevertheless, cohort variation in height within sub-Saharan Africa is sensitive to indicators of the early life nutritional environment (Akachi and Canning, 2007). We have confirmed that this is also the case in the current sample, where birth year GDP, the regional infant mortality rate and the average education of mothers in the cohort influences the height of adult women (Bhalotra 2009).…”
Section: Maternal Healthsupporting
confidence: 72%
“…19,38,39 There is evidence, however, that average modern adult heights have been stagnating or actually declining, particularly in Africa and when considered relative to Western European countries. 17,[59][60][61] Using data from the World Health Surveys (2002)(2003)(2004) 62 to assess these claims, the correlation between mean adult self-reported height and increasing birth cohort (1934-1948; 1949-1963; 1964-1978) representing decreasing age cohorts (55-69, 40-54, and 25-39 years) was calculated. The smallest increases in adult height during this time period occurred in Africa (correlation ¼ 0.01), and the greatest increases in adult height occurred in Europe (correlation ¼ 0.25) (Figure 1).…”
Section: Patterns Of Modern Adult Height Secular Increasesmentioning
confidence: 99%
“…However reductions in infant mortality are correlated with improvements in child health and physical development in the form of adult height (Crimmins and Finch 2006;Akachi and Canning 2007). Microeconomic studies suggest that early childhood health affects physical and cognitive development, educational outcomes, and productivity when the cohort reaches working age (Barker 1992;Bleakley 2003;Behrman and Rosenzweig 2004;Kremer and Miguel 2004;Case, Fertig and Paxson 2005;Heckman 2007;Hoddinott, Maluccio, Behrman, Flores et al 2008;Bleakley 2010;Baird, Hicks, Kremer and Miguel 2011).…”
Section: Introductionmentioning
confidence: 99%